Parenting Patterns as Social Support for Children with Special Needs - Aus Arief Ikhwani Hakim (LP3M STAI MA'ARIF MAGETAN, 2024)
Parenting children with special needs (ABK) requires patience and higher knowledge in order to be able to direct children appropriately. Parents as the main social support who take a role in accompanying ABK grow and develop according to their abilities. This study aims to find out how parenting as social support for children with special needs. The approach in this study is descriptive qualitative with interview methods and observation of parents who have ABK. In this study concluded that the role of parents in parenting children is very important in the development of individuals. However, there are still some parents who do not understand how to provide proper parenting to children with special needs because of lack of knowledge about parenting, which makes it more difficult for children to develop.